Job Satisfaction and Remote Work: Analysis of the Relationship in Professors of a Public University in Puno, Peru - López-Cueva, Lourdes Antonieta (2024)
Objective. To determine the degree of relationship between remote work variables and job satisfaction of the teaching staff of a public university in Puno, Peru. Methodology. The research was developed with a quantitative approach, non-experimental design, and correlational cross-sectional type. The population consisted of 216 professors, using probabilistic sampling a sample of 138 was obtained, the instruments used were the literature review and a questionnaire applied to the participants. In addition, the validity of the questionnaire was tested by expert judgment and Cronbach’s alpha coefficient, the result of which was 0.947. Results. It was found that there is a significant relationship between remote work and job satisfaction (rho=0.658; p<0.05) of the teaching staff. Conclusion. Remote work significantly influences the job satisfaction of the teaching staff of a public university in Puno, Peru.